Generation of Human Induced Pluripotent Stem Cells from Patients with Primary Immune Deficiencies. - Ordovas-Montanes, Jose M. (Tufts Archival Research Center, 2005)
Primary immune deficiencies (PIDs) are a collection of genetically inherited disorders that affect the proper functioning of the immune system. In a traditional sense, PIDs are major defects in one or more of the major leukocyte subsets which commonly lead to a wide array of different recurrent and opportunistic infections eventually resulting in a very premature death. A major paradigm shift has led to an expansion of the classical definition of a PID as an immunological phenotype to a PID as any defect resulting from inherited errors of immunity that can pose a substantial threat to life. Here we describe the generation and characterization of induced pluripotent stem cells (iPSC) created using a polycistronic lentiviral vector (pHAGE-STEMCCA) expressing OCT4, SOX2, KLF4 and cMYC for the study of several PIDs in vitro. We have generated patient-specific iPSC from individuals with T-B-NK+ severe combined immunodeficiency (SCID) or Omenn Syndrome due to RAG1-defiency. We have also generated iPSC from individuals with an exquisite predisposition to herpes simplex encephalitis (HSE) due to defects in STAT1, TLR3, or UNC-93B with undefined cellular defects in immunity within the central nervous system. Due to the pluripotency of iPSC derived from skin fibroblasts, we will be able to study human lymphoid differentiation as well as the responsiveness of human neuronal cells to infection. Due to the inability of studying these processes on human cells in vivo, these in vitro disease models represent novel and powerful tools to study the disease process and attempt to develop therapies for the treatment of these diseases.